Charters, vouchers, and public education - Peterson, Paul E.; Campbell, David E., 1971- (Brookings Institution Press, 2001)
This volume brings together the most current empirical research on two important innovations reshaping American education today -- voucher programs and charter schools. Contributors include many of the foremost analysts in education policy. Of specific significance is cutting-edge research that evaluates the impact of vouchers on academic performance in the New York City, Washington, D.C., and Dayton, Ohio, school systems. The volume also looks beyond the American experience to consider the impact of market-based education as pioneered by New Zealand. Contributors also take stock of the movement's effects on public schools in particular and public opinion at-large. Also provides summaries of the existing research and the legal issues facing school choice.